Imaginologic resources used in diagnosis of root resorptions: comparative study - Paloma Gonçalves CERQUEIRA; Hannah Barros SIMÕES; Maria Cristina Teixeira CANGUSSU; Luis Cardoso RASQUIN; Fabiola Bastos de CARVALHO (RGO: Revista Gaúcha de Odontologia, 2022)
ABSTRACT Objective: Compare the accuracy of early diagnosis of simulated internal root resorptions and external root resorption, using digital periapical radiography and cone beam computed tomography. Methods: Root resorption were simulated in extracted human teeth by demineralization with 5% nitric acid solution and 8% Sodium Hypochlorite in different periods (1 and 5 days). For the group external root resorption (n=12) composite resin cylinders were positioned on middle third of buccal surface of roots, to delimit application of demineralization substances. In group internal root resorptions (n=12) the teeth were sectioned longitudinally, and the composite resin cylinders were positioned in the middle third of root canals. The teeth were mounted in a dry mandible and evaluated by digital radiography and tomography. The images were evaluated by two examiners. Results: Analyzing the tomographic images in period of 1 day, the examiner 2 identified internal root resorptions that were not identified in radiographic images (p<0.05). No examiner was capable of diagnosing external root resorption irrespective of exam, in the group of 1 day (p>0.05). In 5 day period of induction, both exams identified internal root resorptions (p>0.05), however, the tomographic images were more effective in identifying external root resorption (p <0.05) for both examiners. Conclusion: Cone beam computed tomography was shown to be more effective than digital periapical radiography for detecting internal root resorptions with 1 day of induction. The imaginological resources used in this study were not able to early detect external root resorption.